Advances in crash dynamics for aircraft safety. (April 2018) - Guida, M.; Marulo, F.; Abrate, S.
Abstract: This paper studies the ability of the fuselage's lower lobe to absorb the energy during a crash landing, where the introduction of the composite materials can improve the crash survivability thanks to the crushing capability of structural parts to limit the effects of deceleration on the occupants. Providing a protective shell around the occupants and minimizing the risks of injuries during and immediately after the crash in the post-crash regime is a safety requirement. This study consists of: (1) numerical and experimental investigations on small components to verify design concepts using high performance composite materials; (2) analyses of full scale crashes of fuselage lower lobes. This paper outlines an approach for demonstrating the crashworthiness characteristics of the airframe performing a drop test at low velocity impact to validate a numerical model obtained by assembling structural components and materials' properties previously obtained by testing coupons and sub-elements.